Peningkatan Kecepatan Lari Jarak Pendek Melalui Model Bermain Pada Siswa Kelas V SD Negeri 2 Bukit Durian Kota Tidore Kepulauan - Abas, Rudi; Nuryastuti, Triana (Peneliti.net, 2026)
This study aims to improve short-distance running skills, particularly the 80m sprint, after implementing a play model. The instruments used in this study were observation sheets, documentation, and questionnaires. This study used the Classroom Action Research (CAR) method. The population was fifth-grade students of SD Negeri 2 Bukit Durian, Tidore Islands City, and the sample size was 20 students, divided into 7 boys and 13 girls. Through play, students learned short-distance running. This is crucial considering that many students are less enthusiastic and pay less attention during short-distance running lessons. In this study, the researchers collaborated with teachers at SD Negeri 2 Bukit Durian, Tidore Islands City, to plan a learning action that lasted for two cycles. The results showed that students' skills in short-distance running at fifth-grade students of SD Negeri 2 Bukit Durian, Tidore Islands City, improved. The psychomotor aspect of cycle I increased to 59%, and cycle II increased to 82%. The affective aspect increased to 88% in cycle I and 89% in cycle II. The cognitive aspect increased to 6.2% in cycle I and 6.6% in cycle II. The results of the student questionnaire in cycle I were 80%, while in cycle II it increased to 95%. Based on the research results, it can be concluded that learning short distance running with play models can improve students' skills at the school